Draft genome sequence data of Lachancea thermotolerans NIYL22663NCBI - Jeong-Ah Yoon; Jun-Hyeok Park; Hye-Jin Hong; Myoung-Dong Kim (Data in Brief, 2025)
Lachancea thermotolerans NIYL22663, which was isolated from soil, is known for its enhanced production of organic acids and flavor compounds, making it valuable for fermentation and biotechnology applications. Despite these promising traits, its whole genome sequences remain underexplored. In this study, its whole genome was sequenced using the PacBio Sequel II and Illumina platforms. The assembled genome comprises 10 contigs, with a total length of 10,644,170 bp, an N50 of 1,505,420 bp, a GC content of 46.9%, and 5,062 predicted genes. Average Nucleotide Identity (ANI) analysis revealed over 95% similarity with other L. thermotolerans strains, indicating high genomic similarity. However, single-nucleotide polymorphism analysis showed that L. thermotolerans NIYL22663 exhibits a relatively long genetic distance, suggesting potential genetic divergence within the species. These genomic data provide an invaluable foundation for further exploration of the genetic and biochemical characteristics of L. thermotolerans. The genome data have been deposited in the NCBI database under the accession number JBKKGC000000000.1.